Palaeomagnetic, geochronological and geochemical study of Mesoproterozoic Lakhna Dykes in the Bastar Craton, India: Implications for the Mesoproterozoic supercontinent - Pisarevsky, Sergei; Biswal, T.; Wang, Xuan-Ce; De Waele, B.; Ernst, R.; Söderlund, U.; Tait, J.; Ratre, K.; Singh, Y.; Cleve, M. (Elsevier BV, 2013)
Palaeomagnetic analysis of the Lakhna Dykes (Bastar Craton, India) yields a palaeopole at 36.6°N, 132.8°E, dp=12.4°, dm=15.9°, and the U--Pb zircon age obtained from one of the rhyolitic dykes is 1466.4±2.6 Ma (MSWD=0.21, concordia age based on two analyses with identical Pb--U ages), similar to previously published U\Pb ages. Major and trace element analyses of the Lakhna Dykes show shoshonitic and high-K calc-alkaline affinities consistent with a subduction related characteristics suggesting an active continental margin setting. This is in keeping with the Palaeo- to Mesoproterozoic tectonic environments in the eastern Indian margin. The new 1460 Ma Indian palaeopole was used to test possible palaeopositions of India within the Mesoproterozoic supercontinent Columbia. Of the four palaeomagnetically permissible reconstructions, juxtaposing western India against south-west Baltica is geologically the most reliably constrained and best fitting model. Our preferred reconstruction implies a long Palaeo- to Mesoproterozoic accretionary orogen stretching from south-eastern Laurentia through south-western Baltica to south-eastern India. Breakup of India and Baltica probably occurred in the Late Mesoproterozoic, but additional constraints are needed.